Legal Analysis of The Non-Processing Revitalization Project of Jungjang Market in Cirebon Regency - Legian Dwi Ratsa; Mohamad Sigit Gunawan (Riviera Publishing, 2026)
Following the 2015 fire, Jungjang Market was revitalized through a Bangun Guna Serah (BGS), or Build-Operate-Transfer (BOT), partnership between the Jungjang Village Government and PT Dunia Milik Bersama. However, the project has been stalled since August 2023 due to its unilateral termination by the Jungjang Village Government, resulting in losses for investors and traders. This study aims to analyze the authority of the Village Government in the Jungjang Market revitalization project, assess the project termination from the perspective of abuse of authority, and investigate the forms of accountability and legal remedies available to the injured parties. This research employs a normative-empirical legal approach by examining primary legal materials, including Law Number 6 of 2014, Law Number 25 of 2007, Law Number 30 of 2014, and Law Number 31 of 1999, as well as secondary legal materials. The empirical aspect was conducted through interviews with stakeholders, including the Village Government, investors, traders, and relevant agencies, as well as field observations. The results of the study indicate that the Jungjang Village Government had the authority to carry out the BGS/BOT partnership. However, the unilateral termination of the project fulfilled the elements of abuse of authority because it was carried out without a clear legal basis, exceeded the scope of authority, and disregarded the agreed dispute resolution mechanism. Investors may pursue arbitration, civil lawsuits, or lawsuits before the State Administrative Court (Pengadilan Tata Usaha Negara/PTUN), while traders may file claims for compensation.